PHYSIC AND CHEMICAL PROPERTIES OF ALLOYED METALLURGICAL WASTE AS A SECONDARY RESOURCE-SAVING SUBSTANCE - НrigorіevStanislav; Skachkov, Viktor; Berezhnaya, Olga; Anishchenko, Vira (Scientific Journal "Metallurgy", 2021)
The paper analyzes the current state of researches on the chemical and phase composition of industrial waste based on slags of aluminothermic production of ligatures and scale of high-speed steel grade R6M5. The investigations were conducted with slags of aluminothermic production obtained after smelting of refractory ligatures, and also the scale of high-speed steel grade R6M5 was used. X-ray phase analysis was carried out on a DRON-6 diffractometer. Phase composition of slags of aluinothermic production and scale of high-speed steel of Р6М5 brand is ascertned by the method of X-ray phase analysis. Slag samples of aluminothermic production of ligatures contain oxide CaAl4O7, compounds AlV2O4, Al75Mo20W5 and Mo(Si,Al)3. The scale of high-speed steel grade R6M5 is represented by oxides Fe3O4, Fe2O3, FeO and FeWO4. Molybdenum-containing compounds are represented by oxide MoO2 and carbide Mo2C. The microstructure of the investigated technogenic materials has a disordered form and consists of particles of different sizes and shapes. The microstructure of the investigated technogenic materials has a disordered form and consists of particles of different sizes and shapes. The content of tungsten and molybdenum in the investigated areas of scale steel R6M5 was in the range of 3.45…10.73 and 2.17…6.65%. An area with chromium and vanadium content of 1.23 and 1.18% was also detected. The oxygen content in the studied areas was in the range of 8.52…23.16%. In the slag samples of MFTA ligature production, the phases Al75Mo20W5, Mo(Si,Al)3 were detected, which may be present in the form of metal inclusions. Studies of slags of aluminothermic production of smelting of AHM-50 and AMVT ligatures show that the base consists of CaAl4O7. Aluminothermic slag and high-speed steel scale were used as components of the charge for smelting alloying and deoxidizing alloys. The introduction of scale into the charge allows to provide a given the degree of alloying of the alloy with refractory elements. Introduction to the charge of slag aluminothermic production in the range of 4.5…14.5% provided an increase in the alloy of the alloy. There was also some increase in alloy desulfurization.